PENGARUH PERCEIVED OF RISK (PERSEPSI RISIKO) TERHADAP MINAT BELI ONLINE - Nadia Nadia; Nursakinah Ritonga (Program Studi Administrasi Bisnis, 2022)
This study aims to examine the influence of perceived of risk on the online buying interest of the people of Dusun 1 Tambon Tunong Village, Dewantara District, North Aceh Regency. This research was conducted in Hamlet 1 of Tambon Tunong Village, Dewantara District, North Aceh Regency. This study used primary data in the form of questionnaires that were distributed to the people of Dusun 1 Tambon Tunong Village, Dewantara District, North Aceh Regency who made online purchases. The data analysis methods used are instrument tests and classical assumption tests as well as simple linear regression tests using the help of SPSS version 26 software. The results of the partial test showed that the perceived of risk had a positive and significant effect on the online buying interest of the people of Dusun 1 Tambon Tunong Village, Dewantara District, North Aceh Regency.